Climate and competition effects on tree growth in Rocky Mountain forests. (8th May 2017) - Buechling, Arne; Martin, Patrick H.; Canham, Charles D.
Summary: Climate is widely assumed to influence physiological and demographic processes in trees, and hence forest composition, biomass and range limits. Growth in trees is an important barometer of climate change impacts on forests as growth is highly correlated with other demographic processes including tree mortality and fecundity. We investigated the main drivers of diameter growth for five common tree species occurring in the Rocky Mountains of the western United States using nonlinear regression methods. We quantified growth at the individual tree level from tree core samples collected across broad environmental gradients. We estimated the effects of both climate variation and biotic interactions on growth processes and tested for evidence that disjunct populations of a species respond differentially to climate. Relationships between tree growth and climate varied by species and location. Growth in all species responded positively to increases in annual moisture up to a threshold level. Modest linear responses to temperature, both positive and negative, were observed at many sites. However, model results also revealed evidence for differentiated responses to local site conditions in all species. In severe environments in particular, growth responses varied nonlinearly with temperature. For example, in northerly cold locations pronounced positive growth responses to increasing temperatures were observed. In warmer southerly climates, growth responses were unimodal, declining markedly above a threshold temperature level. Net effects from biotic interactions on diameter growth were negative for all study species. Evidence for facilitative effects was not detected. For some species, competitive effects more strongly influenced growth performance than climate. Competitive interactions also modified growth responses to climate to some degree. Synthesis . These analyses suggest that climate change will have complex, species‐specific effects on tree growth in the Rocky Mountains due to nonlinear responses to climate, differentiated growth processes that vary by location and complex species interactions that impact growth and potentially modify responses to climate. Thus, robust model simulations of future growth responses to climate trends may need to integrate realistic scenarios of neighbourhood effects as well as variability in tree performance attributed to differentiated populations. Abstract : These analyses suggest that climate change will have complex, species‐specific effects on tree growth in the Rocky Mountains due to nonlinear responses to climate, differentiated growth processes that vary by location and complex species interactions that impact growth and potentially modify responses to climate. Thus, robust model simulations of future growth responses to climate trends may need to integrate realistic scenarios of neighbourhood effects as well as variability in tree performance attributed to differentiated populations.